1998
DOI: 10.1086/301826
|View full text |Cite
|
Sign up to set email alerts
|

A Susceptibility Locus for Bipolar Affective Disorder on Chromosome 4q35

Abstract: Bipolar affective disorder (BAD) affects approximately 1% of the population and shows strong heritability. To identify potential BAD susceptibility loci, we undertook a 15-cM genome screen, using 214 microsatellite markers on the 35 most informative individuals of a large, statistically powerful pedigree. Data were analyzed by parametric two-point linkage methods under several diagnostic models. LOD scores >1.00 were obtained for 21 markers, with four of these >2.00 for at least one model. The remaining 52 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 28 publications
3
66
2
Order By: Relevance
“…Other chromosomal regions with suggestive linkage peaks in the genome-wide scan showed consistent results with other studies. The suggestive peaks at 4q and 13q are consistent with significant linkage results previously reported by our group in independent Australian BP cohorts, 32,42 while the 6q locus was reported as one of two confirmed BP loci in a genome-wide meta-analysis of 1067 families. 43 The supplementary markers were added to confirm the genome-wide linkage to 15q, and to gain greater location estimates for a BP susceptibility gene around the maximal genome scan marker D15S130.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other chromosomal regions with suggestive linkage peaks in the genome-wide scan showed consistent results with other studies. The suggestive peaks at 4q and 13q are consistent with significant linkage results previously reported by our group in independent Australian BP cohorts, 32,42 while the 6q locus was reported as one of two confirmed BP loci in a genome-wide meta-analysis of 1067 families. 43 The supplementary markers were added to confirm the genome-wide linkage to 15q, and to gain greater location estimates for a BP susceptibility gene around the maximal genome scan marker D15S130.…”
Section: Discussionsupporting
confidence: 91%
“…Four liability classes (class 1, < 20 years; class 2, 20-29 years; class 3, 30-39 years; and class 4, > 40 years) were used in the analyses with maximum age-specific penetrance levels of either 60 or 90%. 32 In the 90% model, liability classes were defined with penetrances of 0.18, 0.45, 0.68 and 0.9; those in the 60% model were defined with penetrances of 0.12, 0.30, 0.45 and 0.6. The data was analysed under both dominant and recessive inheritance models.…”
Section: Genotypingmentioning
confidence: 99%
“…25 Subsequent analysis in our cohort of 55 multigenerational bipolar pedigrees significantly strengthened the evidence for linkage to chromosome 4q35, and haplotype analysis allowed us to define a candidate interval of 43 cM extending to the telomere of chromosome 4q35. 26 Other groups have now independently published support for this region.…”
Section: Introductionmentioning
confidence: 59%
“…In particular, findings in 4p, 4q, 8q, 10p, 12q24, 13q, 18p, 18q, 21q, and 22q have been supported by more than one study. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, these studies have not identified any specific genes, and a recent metaanalysis of available genome scans showed no regions with a conclusive evidence of linkage. 20 The relatively slow progress of gene-mapping efforts is often explained by the 'complex' nature of the illness and of the genotype-phenotype relation.…”
mentioning
confidence: 99%